VD_FINDINFO HC / 2009 / 111 vom 13. Mai 2009 - VD Tribunal cantonal (2009)
DROIT AU SALAIRE, MISE À LA RETRAITE, EMPÊCHEMENTEN GÉNÉRAL, POUVOIR D'EXAMEN LIBRE | 324a al. 1 CO, 324b CO, 452 CPC, 465 al. 1 CPC